Saluran Pemasaran Cabai Rawit di Kecamatan Puger Kabupaten Jember Provinsi Jawa Timur - ATIKATUL FITRIYAH; NI WAYAN PUTU ARTINI; PUTU UDAYANI WIJAYANTI (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2019)
Marketing Channel for Cayenne Pepper in Puger Sub-District Jember Regency East Java Province The difference in the cayenne pepper marketing channels in Puger Sub-District, JemberRegency has an impact on the price for producers and consumers. The selling price ofcayenne pepper at the farm level during the harvest season in July-September 2017continues to decline and the bargaining position of farmers was considered weak. Thepurpose of this study was to find out the marketing institutions and channels, marketingfunctions, marketing efficiency (EP), and the ratio of the cost of cayenne pepper inPuger Sub-District. The data used were qualitative and quantitative data. The analysisused is descriptive qualitative and quantitative methods. The respondents of this studywere 51 farmers (Mojosari, Grenden, and Jambearum Villages) which were determinedby the proportional random sampling method and 15 marketing institution respondentsdetermined by the snowball sampling method.The respondents of the marketinginstitutions consisted of one middleman, four sub-district level collecting traders, threeinter-city traders, and seven retailers. There are three marketing channels namely, (1)farmers- collecting traders - retailers (Balung, Grenden, and Pasar Tanjung markets) -consumers, (2) farmers - collecting traders - inter-city traders (Jakarta) - markets inJakarta, (3) farmers - middleman - collecting traders - inter-city traders (Jakarta) -markets in Jakarta. Every marketing institution performs marketing functions, namelyexchange functions, physical functions, and facility functions. The functions performedby each institution are different. All marketing channels in this study are efficient. Themost efficient marketing institution in the marketing channel I is the collecting traders,onmarketing channels II, namely inter-city traders, and on marketing channelsIII, namely inter-city traders with the same values as in marketing channels II. Eachchannel has a collecting trader. When it was compared, the collecting traders at channelI was the most efficient institution.